PENINGKATAN PENGETAHUAN DAN KETERAMPILAN UMKM JOGOMUKTI MENGGUNAKAN WEBSITE UNTUK UMKM NAIK KELAS DAN TANGGUH - Rochmadi, Tri; Mulyandari, Rita; Ardiyaningrum, Martalia; Miju, Sarwo; Rosadi, Septian Ibnu; Wahyudi, Angga Dwi; Nurlani, Wa Ode; Saputri, Isna Deayanti (Jurnal Abdi Insani, 2025)
The rapid development of digital technology has driven transformation in the Micro, Small, and Medium Enterprises (MSMEs) sector, including the Sedulur Jogomukti community in Jogotirto Village, which still faces limitations in marketing, financial management, and cybersecurity awareness. These conditions formed the basis for implementing an assistance program to enhance the capacity and resilience of MSMEs in the digital era. This study aims to analyze the improvement of MSME competencies through a comparison of pre-test and post-test results after the program. The method applied was a participatory case study consisting of four stages: problem analysis, website development, training and mentoring, and evaluation. Data were collected from 40 MSME participants using a Likert scale questionnaire administered before and after the intervention. The results indicated a significant increase across all measured aspects, including production management, digital marketing, financial management, as well as cybersecurity and disaster risk mitigation. Digital marketing, financial management, and cybersecurity recorded the most substantial improvements compared to the initial conditions. These findings confirm that a holistic mentoring program through the utilization of websites can strengthen both the competitiveness and resilience of MSMEs in facing digital challenges.